GREEN SYNTHESIS OPTIMIZATION AND CHARACTERIZATION OF SILVER NANOPARTICLE SUSING AQUEOUS EXTRACT OF CROCUS SATIVUS L. - NERAN ALI THAMER,; LAMIA A. ALMASHHEDY, (International Journal of Pharma and Bio Sciences, 2014)
Green chemistry means utilization of various plant resources for the synthesis of metallic nanoparticles. In the present study silver nanoparticles was synthesized in a single step by a green biosynthetic method using an extract of Crocus Sativus L act as a reducing and capping agents. The nanoparticles were characterized usingUV-Vis, X-ray diffraction (XRD) and Dynamic light scattering (DLS) .The prepared silver nanoparticles(AgNPs) showed surface Plasmon resonance centered at 440 nm. The XRD pattern showed the face centered cubic structure of silver nanoparticles. The size rangefrom19.9nm to 28.1nm was determined by using laser particle size analyzer. The current research work investigates the findings of optimization of different experimental variable conditions like time,temperature,reaction pH, silver nitrate concentration and the mixing ratio of the reactants on silver nanoparticles synthesized. The optimized condition for the synthesis of silver nanoparticles revealed that silver nitrate concentration was 1 mM, temperature was70°C, PH was 9, incubation time 1 h and aqueous extract and silver nitrate ratio was 5:95.